Performance characteristics and parametric optimizations of a weak dissipative pumped thermal electricity storage system. (1st February 2018) - Guo, Juncheng; Cai, Ling; Yang, Hanxin; Lin, Bihong
Highlights: A more universal model of the pumped thermal electricity storage system is proposed. Main irreversible losses are considered and key operating parameters are introduced. General performance characteristics of the system are revealed. Optimum regions of several important parameters are determined. A generalized model of electrical energy storage systems is further established. Abstract: Based on the weak dissipative assumption, a more universal thermodynamic model of the pumped thermal electricity storage (PTES) system is established, where the main irreversibilities are considered and several key operating parameters are introduced. Analytic expressions for some key performance parameters, e.g., the round trip efficiency (RTE), heat pumping rate, and power output, etc. of the PTES system are derived. The upper boundaries of the RTE at the maximum power output and the maximum RTE for some given parameters are determined. The optimally operating regions of several parameters operating at different modes are determined. Notably, a generalized thermodynamic model of weak dissipative electrical energy storage (EES) systems is proposed, and consequently, the results obtained from the PTES system may be applied directly to reveal the performance characteristics of these EES systems.